2015
DOI: 10.1038/ncomms7610
|View full text |Cite
|
Sign up to set email alerts
|

Sumoylation controls the timing of Tup1-mediated transcriptional deactivation

Abstract: The small ubiquitin-like modifier (SUMO) is implicated in various cellular activities, including transcriptional regulation. We previously showed that the yeast activator Gcn4 becomes sumoylated during activation, facilitating its eventual promoter eviction and transcriptional shut off. Here we show that the corepressor Tup1 is sumoylated, at two specific lysines, under various stress conditions. Mutation of these sites has no effect on Tup1 recruitment or RNAP II promoter occupancy immediately following induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…In another, somewhat related study, sumoylation of the Tup1 transcriptional repressor on K229 and K270 was found to promote binding of Tup1 to the ARG1 promoter . The authors proposed that Tup1 sumoylation mediates the subsequent transcriptional deactivation that is required to downregulate ARG1 expression after the initial burst of transcription.…”
Section: Sumo As a Transcriptional Repressor: The Dogmamentioning
confidence: 97%
“…In another, somewhat related study, sumoylation of the Tup1 transcriptional repressor on K229 and K270 was found to promote binding of Tup1 to the ARG1 promoter . The authors proposed that Tup1 sumoylation mediates the subsequent transcriptional deactivation that is required to downregulate ARG1 expression after the initial burst of transcription.…”
Section: Sumo As a Transcriptional Repressor: The Dogmamentioning
confidence: 97%
“…In a genome-wide study, SUMO was found to be enriched at genes encoding tRNA and ribosomal protein (RP) genes, and sumoylation of the Rap1 transcriptional regulator promotes recruitment of the basal transcription machinery to these genes (Chymkowitch et al, 2015a). Interestingly, SUMO plays an important role not only in transcriptional activation by the Gcn4 transcription factor but also in subsequent transcriptional deactivation through a combination of SUMO-dependent clearance of Gcn4 and stabilization of Tup1 corepressor binding at promoters (Ng et al, 2015). The yeast SUMO proteases also can modulate transcription.…”
Section: Introductionmentioning
confidence: 99%
“…Xenopus Groucho is SUMOylated at multiple sites, and SUMOylation enhances its corepressor activity (Ahn et al, 2009). Similarly, the yeast Groucho ortholog Tup1 has recently been shown to be SUMOylated, and although mutation of its SUMO sites does not affect initial recruitment to target promoters, it does affect its ability to remain on the promoters, suggesting SUMO stabilizes the corepressor complex (Ng et al, 2015). Interestingly, Tup1 interaction partners histone H3, Cti6, Gcn5, Gal11, and Cyc8 also become SUMOylated under similar conditions as Tup1, and SUMO may generally hold together transcriptional repressor complexes in the same manner that SUMO protein functions to hold together DNA repair systems and PML nuclear bodies (Psakhye and Jentsch, 2012; Shen et al, 2006).…”
Section: Discussionmentioning
confidence: 99%